Analysis of Logistics Performance and its Impact on Total Bilateral Trade between Colombia and China (Estudios) - Bustamante Matoma, Harold Anderson (2025)
The purpose of this research was to analyze the logistics performance between Colombia and China and its impact on bilateral trade. The hypothesis regarding how logistics infrastructure and trade policies contribute to the transit of goods was formulated. To achieve this objective, a mixed methodological approach with a predominant quantitative focus was employed. This approach involved conducting a literature review and designing a survey-type instrument. The collected data were processed using the Statistical Package for the Social Sciences (SPSS) Software, version 29.0. The sample consisted of 162 importers selected through a non-probabilistic convenience sampling method. The findings support the hypothesis that emphasizes the necessity for continual improvement of logistical aspects to enhance the nation’s development and competitiveness. In conclusion, the research suggests the importance of fostering agreements and alliances to promote bilateral trade.